Factors Influencing Turnover Intention in Garment Companies: The Role of Job Satisfaction and Work Stress - Hantika, Yul Isnanda Yayan Tri; Efriyani Sumastuti,; Heri Prabowo, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract This study investigates the influence of job satisfaction, organizational commitment, organizational culture, work stress, and work environment on turnover intention among employees in garment companies in Semarang Regency. A total of 100 employees were selected as respondents, and data were collected through a questionnaire and analyzed using SPSS 25. The findings indicate that job satisfaction and work stress significantly impact turnover intention, with higher job satisfaction decreasing the likelihood of employees intending to leave and higher work stress increasing it. On the other hand, organizational commitment, organizational culture, and work environment were found to have no significant effect on turnover intention. These results highlight the importance of enhancing job satisfaction and managing work stress as critical factors in retaining employees and reducing turnover rates. The study suggests that organizations should focus on improving workplace conditions and employee well-being to reduce turnover intention and maintain a stable workforce.